No sleep for Angus - Weir, Rosemary.; Grant, Elisabeth (Abelard-Schuman, 1970)
A twelve-year-old boy, the only witness to a bank robbery, is chased all over London by the thieves.
A twelve-year-old boy, the only witness to a bank robbery, is chased all over London by the thieves.
sap.
Keywords: Thieves / Juvenile fiction.